2009
DOI: 10.1177/0961203309345738
|View full text |Cite
|
Sign up to set email alerts
|

Common infectious agents prevalence in antiphospholipid syndrome

Abstract: Antiphospholipid syndrome is characterized by thrombosis and pregnancy loss. Infections are generally associated with autoimmune diseases, but in the setting of antiphospholipid syndrome this link has been suggested as having a pathogenic role. In this study, 98 patients with antiphospholipid syndrome were screened for antibodies directed to several infectious agents. The main finding in this study is the significantly higher prevalence of IgM antibodies to toxoplasma and rubella. This novel finding suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 55 publications
1
20
0
1
Order By: Relevance
“…2,3 Patients with persistent aPLAs only occasionally present with thrombotic episodes, and sometimes bacterial or viral infections are associated with the clinical manifestations. 4 These observations suggest that the presence of aPLAs alone is not sufficient to promote thrombosis. Most likely, a priming factor of infectious or inflammatory origin is needed.…”
mentioning
confidence: 77%
“…2,3 Patients with persistent aPLAs only occasionally present with thrombotic episodes, and sometimes bacterial or viral infections are associated with the clinical manifestations. 4 These observations suggest that the presence of aPLAs alone is not sufficient to promote thrombosis. Most likely, a priming factor of infectious or inflammatory origin is needed.…”
mentioning
confidence: 77%
“…Previous case reports and case-control studies have linked ATxA with polymyositis [16], rheumatoid arthritis (RA) [17e19], autoimmune thyroid diseases [20,21], Crohn's disease [22], anti phospholipid syndrome [23], Wegener's granulomatosis [24] and autoimmune bullous diseases [25]. While ATxA have been previously associated with SLE [26], subsequent studies challenged this association [27,28].…”
Section: Introductionmentioning
confidence: 95%
“…Parasites in general are considered to be influential immunomodulators, implicated in allergic and autoimmune diseases (Kivity et al, 2009). We recently noticed that serological evidence of T. gondii, specifically, is elevated in several autoimmune diseases, including systemic sclerosis, antiphospholipid syndrome, inflammatory bowel disease, autoimmune thyroid diseases, cryoglobulinemia, and ANCA-associated vasculitides (Arnson et al, 2009;Lidar et al, 2009aLidar et al, , 2009bShapira et al, 2012;Tozzoli et al, 2008;Zinger et al, 2009). Insinuating a potential link to PBC, it was demonstrated that Toxoplasma genome encodes PDC-E2, which is highly represented and exclusively localized inside the parasite apicoplast (a nonphotosynthetic plastid, which is essential for the parasite viability, carbohydrate and fatty acid metabolism) (Fleige et al, 2007).…”
Section: Discussionmentioning
confidence: 99%